2019
DOI: 10.1177/0886260519884689
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault, Campus Resource Use, and Psychological Distress in Undergraduate Women

Abstract: Undergraduate women are at high risk of experiencing sexual assault during their college years. Research has established a strong link between sexual victimization and psychological distress. Although the relationship between sexual victimization and distress has been established, little is known about how the use of university-affiliated sexual assault resources influences mental health outcomes for survivors. The aims of this cross-sectional study were to describe the characteristics of women who used campus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Many of those who disclosed their experiences of violence spoke highly of the CARE Advocates and shared how healing and supportive they were. The association of campus sexual violence resources and increased mental health outcomes has been supported in the literature (Eisenberg et al, 2016;Graham et al, 2019). Because survivors are more likely to report if they receive support from and work with an Advocate and the resulting beneficial mental health outcomes (Dunlap et al, 2018), campus sexual violence resource centers should work to ensure that the number of Advocates adequately serve their campus population to best support survivors and keep perpetrators accountable.…”
Section: Np19483 16mentioning
confidence: 97%
See 1 more Smart Citation
“…Many of those who disclosed their experiences of violence spoke highly of the CARE Advocates and shared how healing and supportive they were. The association of campus sexual violence resources and increased mental health outcomes has been supported in the literature (Eisenberg et al, 2016;Graham et al, 2019). Because survivors are more likely to report if they receive support from and work with an Advocate and the resulting beneficial mental health outcomes (Dunlap et al, 2018), campus sexual violence resource centers should work to ensure that the number of Advocates adequately serve their campus population to best support survivors and keep perpetrators accountable.…”
Section: Np19483 16mentioning
confidence: 97%
“…A substantial body of research confirms that college sexual violence resources, such as CARE, support student survivors through their focus on advocacy and healing. Graham et al (2019) found that college students who utilize these resources after experiencing sexual violence have improved mental health outcomes compared to their peers who did not. The existence of these resources are especially important when considering that survivors are at increased risk of depression, post-traumatic stress disorder (PTSD), suicidal ideation, and substance abuse (Campbell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most literature on CSA has focused on prevalence and prevention efforts, with less research focused on victim-survivors' lived experiences of resilience and post-assault life in the context of campus environments (Brubaker et al, 2017;Fedina et al, 2018;Graham et al, 2019;Moylan & Javorka, 2020;Perkins & Warner, 2017). Research is limited in studying how students practice agency and respond to CSA, including displays of resilience from ecological and strengths-based perspectives (Germain, 2016;Moylan & Javorka, 2020).…”
Section: Csa and Resiliencementioning
confidence: 99%
“…Studies have explored how sexual assault type impacts the likelihood of disclosing to formal and informal sources (Graham et al, 2021; Krebs et al, 2007; Sabina & Ho, 2014). For example, studies have shown that survivors who experienced a forced physical assault were more likely to utilize formal services (Graham et al, 2021; Krebs et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%